Challenging the Industry Effect: Evidence of Fundamental Risk Heterogeneity Across Sectoral and Industry Tiers - Rexon Nainggolan; Ringkot P Nainggolan; Clarijun Q Montebon (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: The study challenges the industry effect concept by analysing total volatility and idiosyncratic risk in the firms listed in the Indonesia equity market to investigate whether firms in the same sector industry share similar risk profiles. Methodology: While previous work has largely focused on the time series of average idiosyncratic volatility, the study uses a novel cross-sectional approach to identify industry-wide mispricing in the normalisation of both total and idiosyncratic volatility, by using data from 601 publicly traded firms in the Indonesia Equity Market (IDX) and several robust statistical tests, including the Coefficient of Variance, the Shapiro-Wilk Test for Data Normality, the Kruskal-Wallis H test, and Levene's Test. Result: The findings show significant variation across industries, with coefficients of variation for total volatility and idiosyncratic risk at the market level higher than typically observed in homogeneous groups. Deviating from the traditional Structure-Conduct-Performance (SCP) view. Conclusions: This study found that the traditional Structure-Conduct-Performance (SCP) model is too simple to capture how firms really behave, especially when compared to the Resource-Based View (RBV) using modern risk analysis. Limitations: The study focuses on standard deviation and STEY X as measures of risk and does not cover other external factors, such as macroeconomic or geopolitical factors. Contributions: The results contribute to the existing capital market literature by providing empirical evidence that challenges the traditional concept of the industry effect, showing that sectoral and industry classifications fail as measures of firm risk profile.